Neuroimaging. - Masdeu, Joseph C.; Gonzalez, R. G. (Ramon Gilberto) (Handbook of clinical neurology, 2016)
Neuroimaging, Part One, a text from The Handbook of Clinical Neurology illustrates how neuroimaging is rapidly expanding its reach and applications in clinical neurology. It is an ideal resource for anyone interested in the study of the nervous system, and is useful to both beginners in various related fields and to specialists who want to update or refresh their knowledge base on neuroimaging. This first volume specifically covers a description of imaging techniques used in the adult brain, aiming to bring a comprehensive view of the field of neuroimaging to a varying audience. It brings broad coverage of the topic using many color images to illustrate key points. Contributions from leading global experts are collated, providing the broadest view of neuroimaging as it currently stands. For a number of neurological disorders, imaging is not only critical for diagnosis, but also for monitoring the effect of therapies, and the entire field is moving from curing diseases to preventing them. Most of the information contained in this volume reflects the newness of this approach, pointing to this new horizon in the study of neurological disorders.